Investing in Social Development - Economic Policy Research Centre (Economic Policy Research Centre, 2021)
In line with the change in the budgeting approach from sector to programme based budgeting, the social development sector lies under the Governance and Security programme, the Human Capital Development and the Community Mobilization and Mindset Change programmes of the third National Development Plan. This brief therefore assesses the contribution of the social development sector to the new Governance and Security programme as articulated in the NDPIII